Vertically Expanded Crystalline Porous Covalent Organic Frameworks - Xie, Shuailei; Addicoat, Matthew A.; Jiang, Donglin (Journal of the American Chemical Society, 2024)
Covalent organic frameworks (COFs) can be developed for molecular confinement and separation. However, their proximate π stacks limit the interlayer distance to be only 3–6 Å, which is too small for guests to enter. As a result, COFs block access to the x–y space and limit guest entry/exit strictly to only the pores along the z direction. Therefore, the extended faces of each layer are hidden between layers, precluding any interactions with guest molecules. Here, we report a strategy for opening interlayer spaces of COFs to attain newly accessible nanospaces between layers. This becomes possible using coordination bonds to replace the conventional π–π stacks between layers. We demonstrate this concept by synthesizing two-dimensional covalent cobalt(II) porphyrin layers through topology-guided polymerization, which were piled up by bidentate axial pillars through coordination bonds with cobalt(II) porphyrin along the z direction, assembling vertically expanded COFs via a one-pot reaction. The resultant frameworks separate the layers with axial pillars and create discrete apertures between layers defined by the molecular length of the pillars. Consequently, the originally inaccessible interlayers are open for guest access, while the polygonal π planes are exposed to trigger various supramolecular interactions. Vapor sorption, breakthrough experiments, and computational studies mutually revealed that the vertically expanded frameworks with optimal interlayer slits induce additional interactions to discriminate benzene and cyclohexane and separate their mixtures efficiently under ambient conditions.